Fussy feeders: phyllosoma larvae of the Western Rocklobster (Panulirus cygnus) demonstrate prey preference. - Megan I Saunders; Peter A Thompson; Andrew G Jeffs; Christin Säwström; Nikolas Sachlikidis; Lynnath E Beckley; Anya M Waite (PLoS ONE, 2012)
The Western Rocklobster (Panulirus cygnus) is the most valuable single species fishery in Australia and the largest single country spiny lobster fishery in the world. In recent years a well-known relationship between oceanographic conditions and lobster recruitment has become uncoupled, with significantly lower recruitment than expected, generating interest in the factors influencing survival and development of the planktonic larval stages. The nutritional requirements and wild prey of the planktotrophic larval stage (phyllosoma) of P. cygnus were previously unknown, hampering both management and aquaculture efforts for this species. Ship-board feeding trials of wild-caught mid-late stage P. cygnus phyllosoma in the eastern Indian Ocean, off the coast of Western Australia, were conducted in July 2010 and August-September 2011. In a series of experiments, phyllosoma were fed single and mixed species diets of relatively abundant potential prey items (chaetognaths, salps, and krill). Chaetognaths were consumed in 2-8 times higher numbers than the other prey, and the rate of consumption of chaetognaths increased with increasing concentration of prey. The highly variable lipid content of the phyllosoma, and the fatty acid profiles of the phyllosoma and chaetognaths, indicated they were from an oligotrophic oceanic food chain where food resources for macrozooplankton were likely to be constrained. Phyllosoma fed chaetognaths over 6 days showed significant changes in some fatty acids and tended to accumulate lipid, indicating an improvement in overall nutritional condition. The discovery of a preferred prey for P. cygnus will provide a basis for future oceanographic, management and aquaculture research for this economically and ecologically valuable species.